Stable and Sustainable Global Tax Coordination with Leviathan Governments - Thomas Eichner; Rüdiger Pethig (Center for Economic Studies and ifo Institute (CESifo), 2014)
Itaya et al. (2014) study the conditions for sustainability and stability of capital tax coordination in a repeated game model with tax-revenue maximizing governments. One of their major results is that the grand tax coalition is never stable and sustainable. The purpose of this note is to prove that there are conditions under which the grand tax coalition is stable and sustainable in Itaya et al.'s model.
Keywords: H71; H77; 330; global tax coordination; repeated game; sustainability; stability